Assessing Mental Health Crisis in Pandemic Situation With Computational Intelligence (Informatica, 2023)
Covid-19 pandemic has created huge emotional distress and increased the risk of psychiatric problems. This happened owing to imposition of necessary stringent healthcare measures that infringed personal space, emotional freedom, and caused financial loss. Our physical well-being is directly associated with mental fitness and health. From analysis it has been found that feature like struggling in concentration and memory, visionary issues, and arthritis are customary symptoms in patients suffering from mental crises. Our proposed research work aims to find out the reasons behind mental illness and ways to improve mental disorders using supervised approach. The main focus is to develop a smart computationally intelligent model to assist healthcare practitioners in analysing and diagnosing severe mental illness. Our proposedmodel assists in analysing causes of mental disorder and aids in reducing total medicinal cost along with reduced mental illness rate. Additionally, a recommendation system is also developed for diagnosing depressive patients.